(3QSGdI aj bGYOI ef edc TjkFGs - (3GdCfUGQj, eQJVi GdCfUGQj, eQJVi Hf eMeO Cejf GdORahdj GdCfUGQj, J (B1281(3g` (B1864(3es ((3cQHdGAs)
(3ChdgG (B:s
(3ChdgG(B: (3GdMeO ddg QH GdYGdejf (B... (3abO GTJgQ aj CdSfI GdabgGA ef ReGf GdTjN (B.. (3Edi ReGffG gPG bVjI cdjI jPcQhfgG aj ebGe GdGSJOdGd HgG Ydi eG jJaQY YdjgGs
(3BNQgG (B:s
(3BNQgG(B: (3hdcf GdXghQ GdePchQ dG MLjI ajg HfaSg MJi jbOe Ydi ebGHdI ef GdCUhd hGdbhGYO GdebQQI Hd jMJGL Edi bjGe Odjd Ydjg Ch GSJfHGW ef COdI GdbhGYO GdCNQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 201s
(3GdPQjYI, L (B17: 10s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis